História e memória da peste suína africana no Brasil,1978-1984: passos e descompassos - Francisco Cecilio Viana (2004)
Aiming to ransom the history and memory of the African swine fever in Brazil, this dissertation not only analyses the letters, reports and other official documents in this field, but also interviews 18 key persons . Half-structured guide lines were also sent to 434 veterinarians, 25hog raiser associations, 43 production companies and cooperatives involved with the hog raising business. The structure of the sanitary care has been analyzed from the point of view of the new history, encompassing the period between 1500 and 1984. Considering the importance of animal production in Brazil, one can find out that, all along, the sanitary legislation for animals was often disregarded due to the interest of certain hog raiser groups in importing animals. Thusone cannot impute to hazard the outbreak of the African swine fever in Brazil. In May, 1978,leftovers of food which had been served in international flights were clandestinely switched over from Galeão International Airport to a private hog raising farrm in Paracambi, Rio de Janeiro State, originating a boom of the African swine fever. This fact revealed the vulnerability of the national sanitary care. The final diagnosis was established by the Plum Island Animal Disease Center, in the United States, on the 1st of June, 1978. Thanks to the efforts of the Ministry ofAgriculture, the initial focus was eradicated, however secondary cases started to be registered in several municipalities of Rio de Janeiro State. The almost simultaneously dissemination of the disease to other regions of the country, and with no correspondence to the expected clinical findings, called the attention of technicians and hog raisers, who believed they were subacute and chronic cases of the classical swine fever. Based on hog raisers, technicians and key persons testimonies and on consultation to other documental sources, I conclude that the African swine fever only existed in the Paracambi municipality and that the other cases observed in other parts of the country corresponded to false-positive serologic diagnosis.